Ethibond suture with underlying infection - A knotty complication - Ganesh Singh Dharmshaktu; Naveen Agarwal; Ishwar Singh Dharmshaktu (Wolters Kluwer Medknow Publications, 2022)
The surgical site infection is a therapeutic challenge and requires additional interventions, prolonged treatment, and increased health-care expenditure. Superficial infections are easier to treat with debridement, regular dressing, and an appropriate antibiotic regimen. Retained and buried sutures are an occasional source of infection and are reported in the literature. Braided nonabsorbable sutures like Ethibond may be the uncommon reason for adjacent area infection that may present later as nonhealing draining sinuses. We report one such encounter in which an adult patient with chronic nonhealing sinuses over the proximal tibia region underwent debridement to unearth embedded sutures used in previous surgery, the removal of which led to gradual recovery and healing of wounds.